Single-Cell RNA and ATAC Sequencing Reveal Hemodialysis-Related Immune Dysregulation of Circulating Immune Cell Subpopulations - Wu, Hongwei; Dong, Jingjing; Yu, Haiyan; Wang, Kang; Dai, Weier; Zhang, Xinzhou; Hu, Nan; Yin, Lianghong; Tang, Donge; Liu, Fanna; Dai, Yong (Frontiers in Immunology, 2022)
Background: An increased risk of infection, malignancy, and cardiovascular diseases in maintenance hemodialysis patients is associated with hemodialysis-related immunity disturbances. Although defects in T-lymphocyte-dependent immune responses and preactivation of antigen-presenting cells have been documented in hemodialysis patients, the effects of long-term hemodialysis on the transcriptional program and chromosomal accessibility of circulating immune cell subpopulations remain poorly defined. Methods: We integrated single-cell RNA sequencing (scRNA-seq) and single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) to characterize the transcriptome profiles of peripheral mononuclear cells (PBMCs) from healthy controls and maintenance hemodialysis patients. Validation of differentially expressed genes in CD4+ T cells was performed by magnetic bead separation and quantitative real-time PCR. Results: We identified 16 and 15 PBMC subgroups in the scRNA-seq and scATAC-seq datasets, respectively. Hemodialysis significantly suppressed the expression levels of T cell receptor (TCR) genes in CD4+ T cell subsets (e.g., TRAV4, CD45, CD3G, CD3D, CD3E) and major histocompatibility complex II (MHC-II) pathway-related genes in monocytes (HLA-DRB1, HLA-DQA2, HLA-DQA1, HLA-DPB1, IFI30, CTSS). Downstream pathways of TCR signaling, including PI3K-Akt-mTOR, MAPK, TNF, and NF-κB pathways, were also inhibited in CD4+ T cell subpopulations during the hemodialysis procedure. Notably, hemodialysis altered cellular communication patterns between PBMC subgroups, particularly TGFBR, BTLA, and CD4 signalings between CD4+ T cells and monocytes. Additionally, we found that hemodialysis inhibited the expression of AP-1 family transcription factors (JUN, JUND, FOS, FOSB) by interfering with the chromatin accessibility profile. Conclusions: Our study provides a valuable framework for future investigations of hemodialysis-related immune dysregulation and identifies potential therapeutic targets for reconstituting the circulating immune system in maintenance hemodialysis patients.